Responses to the tremor of March 4, 1904 through Lima journalistic coverage - Villegas La Chira, Miriam (2023)
The earthquake of March 4th, 1904, as a natural phenomenon, evidenced the vulnerability in the construction materials of the buildings in Lima. This type of study brings us closer to those of historical seismology as long as its relationship as a natural phenomenon with society is analyzed in a diachronic way. Thus, it is also important to point out that studies of natural disasters have as their main purpose the implementation of measures that contribute to reduce the vulnerability of the populations that are frequently affected by them, so as to prevent the effects. For this study, newspaper articles describing the phenomenon and its effects were used as the main sources. Despite the fact that this phenomenon did not generate a disaster with a high number of victims and losses, the authorities and the population did not take the necessary measures to modify the construction patterns, construction materials and territorial ordering with preventive intentions in the future, maintaining and even increasing the vulnerability in the city.